Bone formation in peri-implant defects grafted with microparticles: a pilot animal experimental study - Moest, Tobias; Koehler, Franz; Prechtl, Christopher; Schmitt, Christian; Watzek, Georg; Schlegel, Andreas (Journal of Clinical Periodontology, 2014)
This study aimed to evaluate the healing of peri-implant defects grafted with microparticles (MPs).Six domestic pigs received nine standardized defects at the calvaria, and an implant was inserted in the middle of each defect. The space between the implant and lateral bone portion was filled with MP pellets (n = 18) or MP supernatant (n = 18) or left unfilled (n = 18). After 14 and 28 days, three animals were sacrificed and specimens removed for further processing. Samples were microradiographically and histologically analysed. In addition, we immunohistochemically stained for anti-vWF as a marker of angiogenesis.In the case of bone regeneration and vessel formation, the null hypothesis can be partially rejected. After 14 and 28 days, no significant difference was observed within groups regarding de novo bone formation, bone density and osseointegration. However, superior vessel formation was found at both time points.Microparticles represent a promising treatment option to accelerate peri-implant vessel formation. Further studies are needed to investigate the regenerative properties of MPs more precisely.
EVALuna2:24388

Corrigendum to "The influence of different abutment materials on tissue regeneration after surgical treatment of peri-implantitis - A randomized controlled preclinical study" [J Cranio-Maxillo-Facial Surg 45 (2017) 1190-1196] - Moest, Tobias; Wrede, Jan; Schmitt, Christian; Stamp, Melanie; Neukam, Friedrich Wilhelm; Schlegel, Andreas (Journal of Cranio-Maxillofacial Surgery, 2017)
EVALuna2:24445

Effect of deproteinized bovine bone matrix coverage on the resorption of iliac cortico-spongeous bone grafts - a prospective study of two cohorts - Wiltfang, Joerg; Jaetschmann, Nadine; Hedderich, Juergen; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Gierloff, Matthias (Clinical Oral Implants Research, 2014)
The augmentation of the alveolar ridge using iliac cortico-spongeous bone grafts is routinely used. However, bone grafts show a substantial degree of resorption, which may negatively affect the long-term success of dental implants in the augmented area. The aim of this study was to evaluate the effect of a deproteinized bovine bone matrix coverage on the resorption of iliac bone grafts.Two cohorts consisting of 40 patients who received a vertical augmentation of the alveolar ridge with onlay grafts from the iliac crest were prospectively investigated over a period of 2 years. In half of the patients (n = 40), the grafts were covered by a thin layer of deproteinized bovine bone matrix (DBBM cohort). The other 40 patients received the identical surgical procedure without a DBBM coverage (non-DBBM cohort). The graft height/resorption was radiographically determined immediately after surgery, 6 months, 1 year, and 2 years postoperatively.The height of the bone graft 6 months after surgery accounted 92.15% of the initial value in the DBBM cohort and 87.76% in the non-DBBM cohort. One year after augmentation, the height reduced to 83.95% in the DBBM cohort and 72.92% in the non-DBBM cohort. Two years after surgery, the resorption slowed down and the height of the grafts accounted 81.27% in the DBBM cohort and 71.43% in the non-DBBM cohort. The difference was statistically significant.Deproteinized bovine bone matrix reduces the postoperative resorption of iliac bone block grafts and may therefore enhance the long-term implant prognosis in the augmented area.
EVALuna2:24346

Effects of Bioglass and ß-TCP containing three-dimensional laser sintered polyetheretherketone composites on osteoblasts in vitro - von Wilmowsky, Cornelius; Vairaktaris, Eleftherios; Pohle, Dirk; Rechtenwald, Thomas; Lutz, Rainer; Münstedt, Helmut; Koller, Garrit; Schmidt, Michael; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Nkenke, Emeka (Journal of Biomedical Materials Research Part A, 2007)
LFT Import::2019-07-16 (1422)

Expression of transforming growth factor beta 1-related signaling proteins in irradiated vessels - Preidl, Raimund; Moebius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Schlegel, Andreas; Wehrhan, Falk (Strahlentherapie und Onkologie, 2015)
Microvascular free tissue transfer is a standard method in head and neck reconstructive surgery. However, previous radiotherapy of the operative region is associated with an increased incidence in postoperative flap-related complications and complete flap loss. As transforming growth factor beta (TGF-?) 1 and galectin-3 are well known markers in the context of fibrosis and lectin-like oxidized low-density lipoprotein 1 (LOX-1) supports vascular atherosclerosis, the aim of this study was to evaluate the expression of TGF-?1 and related markers as well as LOX-1 in irradiated vessels.To evaluate the expression of galectin-3, Smad 2/3, TGF-?1, and LOX-1, 20 irradiated and 20 nonirradiated arterial vessels were used for immunohistochemical staining. We semiquantitatively assessed the ratio of stained cells/total number of cells (labeling index).Expression of galectin-3, Smad 2/3, and TGF-?1 was significantly increased in previously irradiated vessels compared with nonirradiated controls. Furthermore, LOX-1 was expressed significantly higher in irradiated compared with nonirradiated vessels.Fibrosis-related proteins like galectin-3, Smad 2/3, and TGF-?1 are upregulated after radiotherapy and support histopathological changes leading to vasculopathy of the irradiated vessels. Furthermore, postoperative complications in irradiated patients can be explained by increased endothelial dysfunction caused by LOX-1 in previously irradiated patients. Consequently, not only TGF-?1 but also galectin-3inhibitors may decrease complications after microsurgical tissue transfer.
EVALuna2:24387

Group 2 ITI Consensus Report: Prosthodontics and implant dentistry - Morton, Dean; Gallucci, German; Lin, Wei-Shao; Pjetursson, Bjarni; Polido, Waldemar; Roehling, Stefan; Sailer, Irena; Aghaloo, Tara; Albera, Hugo; Bohner, Lauren; Braut, Vedrana; Buser, Daniel; et al. (Clinical Oral Implants Research, 2018)
OBJECTIVES: Working Group 2 was convened to address topics relevant to prosthodontics and dental implants. Systematic reviews were developed according to focused questions addressing (a) the number of implants required to support fixed full-arch restorations, (b) the influence of intentionally tilted implants compared to axial positioned implants when supporting fixed dental prostheses (FDPs), (c) implant placement and loading protocols, (d) zirconia dental implants, (e) zirconia and metal ceramic implant supported single crowns and (f) zirconia and metal ceramic implant supported FDPs. MATERIALS AND METHODS: Group 2 considered and discussed information gathered in six systematic reviews. Group participants discussed statements developed by the authors and developed consensus. The group developed and found consensus for clinical recommendations based on both the statements and the experience of the group. The consensus statements and clinical recommendations were presented to the plenary (gathering of all conference attendees) and discussed. Final versions were developed after consensus was reached. RESULTS: A total of 27 consensus statements were developed from the systematic reviews. Additionally, the group developed 24 clinical recommendations based on the combined expertise of the participants and the developed consensus statements. CONCLUSIONS: The literature supports the use of various implant numbers to support full-arch fixed prostheses. The use of intentionally tilted dental implants is indicated when appropriate conditions exist. Implant placement and loading protocols should be considered together when planning and treating patients. One-piece zirconia dental implants can be recommended when appropriate clinical conditions exist although two-piece zirconia implants should be used with caution as a result of insufficient data. Clinical performance of zirconia and metal ceramic single implant supported crowns is similar and each demonstrates significant, though different, complications. Zirconia ceramic FDPs are less reliable than metal ceramic. Implant supported monolithic zirconia prostheses may be a future option with more supporting evidence.
EVALuna2:214274

Implants in bone: Part I. A current overview about tissue response, surface modifications and future perspectives - von Wilmowsky, Cornelius; Moest, Tobias; Nkenke, Emeka; Stelzle, Florian; Schlegel, Andreas (Oral and maxillofacial surgery, 2014)
The aim of study paper is to present an overview of osseointegration of dental implants, focusing on tissue response, surface modifications and future perspective.Great progress has been made over the decades in the understanding of osseous peri-implant healing of dental implants, leading to the development of new implant materials and surfaces. However, failures and losses of implants are an indicator that there is room for improvement. Of particular importance is the understanding of the biological interaction between the implant and its surrounding bone.The survival rates of dental implants in bone of over 90 % after 10 years show that they are an effective and well-established therapy option. However, new implant materials and surface modifications may be able to improve osseointegration of medical implants especially when the wound healing is compromised. Advanced techniques of evaluation are necessary to understand and validate osseointegration in these cases. An overview regarding the current state of the art in experimental evaluation of osseointegration of implants and implant material modifications will be given in Part II.
EVALuna2:24353

Implants in bone: Part II. Research on implant osseointegration : Material testing, mechanical testing, imaging and histoanalytical methods - von Wilmowsky, Cornelius; Moest, Tobias; Nkenke, Emeka; Stelzle, Florian; Schlegel, Andreas (Oral and maxillofacial surgery, 2014)
In order to determine whether a newly developed implant material conforms to the requirements of biocompatibility, it must undergo rigorous testing. To correctly interpret the results of studies on implant material osseointegration, it is necessary to have a sound understanding of all the testing methods. The aim of this overview is to elucidate the methods that are used for the experimental evaluation of the osseointegration of implant materials.In recent decades, there has been a constant proliferation of new materials and surface modifications in the field of dental implants. This continuous development of innovative biomaterials requires a precise and detailed evaluation in terms of biocompatibility and implant healing before clinical use. The current gold standard is in vivo animal testing on well validated animal models. However, long-term outcome studies on patients have to follow to finally validate and show patient benefit.No experimental set-up can provide answers for all possible research questions. However, a certain transferability of the results to humans might be possible if the experimental set-up is carefully chosen for the aspects and questions being investigated. To enhance the implant survival rate in the rising number of patients with chronic diseases which compromise wound healing and osseointegration, dental implant research on compromised animal models will further gain importance in future.
EVALuna2:24335

Long-term outcomes after vestibuloplasty with a porcine collagen matrix (Mucograft(®) ) versus the free gingival graft: a comparative prospective clinical trial - Schmitt, Christian M.; Moest, Tobias; Lutz, Rainer; Wehrhan, Falk; Neukam, Friedrich Wilhelm; Schlegel, Andreas (Clinical Oral Implants Research, 2015)
Porcine collagen matrices are proclaimed being a sufficient alternative to autologous free gingival grafts (FGG) in terms of augmenting the keratinized mucosa. The collagen matrix Mucograft(®) (CM) already showed a comparable clinical performance in the early healing phase, similar histological appearance, and even a more natural appearance of augmented regions. Predictability for long-term stability does not yet exist due to missing studies reporting of a follow-up >6 months.The study included 48 patients with atrophic edentulous or partially edentulous lower jaw situations that had undergone an implant treatment. In the context of implant exposure, a vestibuloplasty was either performed with two FGGs from the palate (n = 21 patients) or with the CM (n = 27 patients). Surgery time was recorded from the first incision to the last suture. Follow-up examinations were performed at the following time points: 10, 30, 90, and 180 days and 1, 2, 3, 4, and 5 years after surgery. The width of keratinized mucosa was measured at the buccal aspect of each implant, and augmented sites were evaluated in terms of their clinical appearances (texture and color).The groups showed similar healing with increased peri-implant keratinized mucosa after surgery (FGG: 13.06 mm ± 2.26 mm and CM: 12.96 mm ± 2.86 mm). The maximum follow-up was 5 years (5 patients per group). After 180 days, the width of keratinized mucosa had decreased to 67.08 ± 13.85% in the FGG group and 58.88 ± 14.62% in the CM group with no statistically significant difference. The total loss of the width of keratinized mucosa after 5 years was significant between the FGG (40.65%) and the CM group (52.89%). The CM group had significantly shorter operation times than the FGG group. Augmented soft tissues had a comparable clinical appearance to adjacent native gingiva in the CM group. FGGs could still be defined after 5 years.The FGG and the CM are both suitable for the regeneration of the peri-implant keratinized mucosa with a sufficient long-term stability. With the CM, tissue harvesting procedures are invalid, surgery time can be reduced, and regenerated tissues have a more esthetic appearance.
EVALuna2:24404

Morphological zeta-potential variation of nanoporous anodic alumina layers and cell adherence - Pedimonte, Birgit; Moest, Tobias; Luxbacher, Thomas; von Wilmowsky, Cornelius; Fey, Tobias; Schlegel, Andreas; Greil, Peter (Acta Biomaterialia, 2014)
Nanoscale surface modification of biomedical implant materials offers enhanced biological activity concerning protein adsorption and cell adherence. Nanoporous anodic alumina oxide (AAO) layers were prepared by electrochemical oxidation of thin Al-seed layers in 0.22 M C2H2O4, applying anodization voltages of 20-60 V. The AAO layers are characterized by a mean pore diameter varying from 15 to 40 nm, a mean pore distance of 40-130 nm, a total porosity of similar to 10% and a thickness of 560 +/- 40 nm. Zeta potential and isoelectric point (iep) were derived from streaming potential measurements and correlated to the topology variation of the nanoporous AAO layers. With decreasing pore diameter a shift of iep from similar to 7.9 (pore diameter 40 nm) to similar to 6.7 (pore diameter 15 nm) was observed. Plain alumina layers, however, possess an iep of similar to 9. Compared to the plain alumina surface an enhanced adherence and activity of hFOB cells was observed on the nanoporous AAO after 24 h culture with a maximum at a pore size of 40 nm. The topology-induced change of the electrochemical surface state may have a strong impact on protein adsorption as well as on cell adhesion, which offers a high potential for the development of bioactive AAO coatings on various biomaterial substrates. (C) 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights
Keywords: Nanoporous alumina; Zeta potential; Isoelectric point; Cell activity

Peri-implant defect regeneration in the diabetic pig: A preclinical study - von Wilmowsky, Cornelius; Schlegel, Andreas; Baran, Christoph; Nkenke, Emeka; Neukam, Friedrich Wilhelm; Moest, Tobias (Journal of Cranio-Maxillofacial Surgery, 2016)
The study aims to establish a peri-implant dehiscence-type bone defect in a diabetic animal model of human bone repair and to quantify the influence of diabetes on peri-implant bone regeneration.Experimental diabetes was induced in three domestic pigs by streptozotocin. Three animals served as healthy controls. After 12 months four standardized peri-implant dehiscence bone defects were surgically created in the ramus mandibulae. The animals were sacrificed after 90 days. Samples were histologically analyzed to quantify new bone height (NBH), bone-to-implant-contact (BIC), area of newly formed bone (NFB), bone-density (BD), and bone mineralization (BM) in the prepared defect (-D) and in a local control region (-L).After 90 days, diabetic animals revealed a significantly lower BIC (p = 0.037) and BD (p = 0.041) in the defect area (-D). NBH and BM-D differences within the groups were not significant (p > 0.05). Significant more NFB was measured in the healthy control group (p = 0.046). In the region of local bone BIC-L was significant less in the diabetic group (p = 0.028). In the local control region BD-L and BM-L was lower in the diabetic group compared to the healthy control animals (p > 0.05).Histological evidence indicates impaired peri-implant defect regeneration in a diabetic animal model.
EVALuna2:24420

The bone-metal interface of defect and press-fit ingrowth of microwave plasma-chemical vapor deposition implants in the rabbit model - Rupprecht, Stephan; Bloch-Birkholz, Alexandra; Lethaus, Bernd; Rosiwal, Stefan; Neukam, Friedrich Wilhelm; Schlegel, Andreas (Clinical Oral Implants Research, 2005)
Keywords: Bone-metal interface; Defect healing; Diamond coating; Implant; MWP-CVD